Effect of Tree‐Fall Gaps on Fruit‐Feeding Nymphalid Butterfly Assemblages in a Peruvian Rain Forest. (4th July 2013) - Pardonnet, Sylvia; Beck, Harald; Milberg, Per; Bergman, Karl‐Olof
Abstract: One of the main natural disturbances that affects the structure of rain forests is treefalls, frequently resulting in gaps. Tree‐fall gaps can bring drastic changes in environmental conditions compared with the undisturbed understory. We investigated the effect of tree‐fall gaps on fruit‐feeding butterfly (Nymphalidae) species assemblages in an undisturbed lowland rain forest in southeastern Peru. We used fruit‐baited traps suspended 2 m above ground in 15 tree‐fall gaps ranging in area from 100 to 1000 m 2 and in adjacent undisturbed understory. Our data support the hypothesis that tree‐fall gap and understory habitats are utilized by different butterfly species assemblages. There were morphological differences between gap and understory species, where the understory species had a larger wing area to thoracic volume. Vegetation structure and composition were important factors affecting the butterfly assemblages. Most of the butterfly species showed an avoidance of vines and a strong association with the presence of trees and shrubs in gaps. There were also differences among gap assemblages that increased with gap size. Some of the species that were associated with gaps have been considered as canopy species. Other gap species in the present study, however, are known to feed on fruits and/or use host plants mainly, or only, occurring in gaps, implicating that the gap assemblage is a mix of canopy species and those unique to gaps. This indicates that, in an undisturbed Amazon forest, tree‐fall gaps may contribute to maintain species diversity by creating a mosaic of specific habitats and resources that favors different butterfly assemblages.